A Critical Review on the Book Public Policy Making Process - Karim Mehri; Sina Samadzadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book Public Policy Making Process written by respected professors Dr. Gholamreza  Esghandari, Karim Eskandari, and Rasoul Eskandari has been an attempt to reduce the resources of the policy-making process. The purpose of this article is to analyze and express the strengths and weaknesses of the book content. The book has advantages, but it also suffers from some shortcomings, the elimination of which can add to the richness of the book's topics. The authors of the book have been careful in the use of specialized terms and equivalence of foreign words, except for a few cases, and are acceptable in terms of compliance with the approved chapters. The content is compatible with scientific values and theories are not addressed.